Effect of Direct Ligament Repair and Tenodesis Reconstruction on Simulated Subtalar Joint Instability. (March 2017) - Choisne, Julie; Hoch, Matthew C.; Alexander, Ian; Ringleb, Stacie I.
Background: Subtalar instability is associated with up to 80% of patients presenting with chronic ankle instability but is often not considered in the diagnosis or treatment. Operative procedures to repair ankle instability have shown good clinical results, but the effects of these reconstruction procedures on isolated subtalar instability are not well understood. The goal of this study was to investigate the effect of the Gould modification of the Broström procedure and a new tenodesis reconstruction procedure on ankle and subtalar joint kinematics after simulating a subtalar injury. Methods: Kinematic data were collected on 7 cadaveric ankles during inversion through the range of ankle flexion and during internal rotation. Testing was performed on the intact foot; after sectioning the calcaneofibular ligament, cervical ligament, and interosseous talocalcaneal ligament; after the Gould modification of the Broström procedure was performed; and after tenodesis was performed and sutures from the Gould modification removed. Results: The Gould modification of the Broström procedure significantly decreased subtalar and ankle inversion motion and subtalar internal rotation compared to the unstable condition. The tenodesis method restricted internal rotation at the subtalar joint and ankle inversion compared to the intact state. Conclusion: Both operative procedures improved stability of the ankle complex, but tenodesis was unable to restore subtalar inversion and restricted ankle inversion in maximum plantarflexion. Clinical Relevance: The Gould modification of Broström ligament repair may be a favorable operative procedure for the restoration of subtalar and ankle joint kinematics.